H2A.B facilitates transcription elongation at methylated CpG loci - Chen, Yibin; Chen, Qiang; McEachin, Richard C.; Cavalcoli, James D.; Yu, Xiaochun

(untitled) (Genome Research, 2014)
H2A.B is a unique histone H2A variant that only exists in mammals. Here we found that H2A.B is ubiquitously expressed in major organs. Genome-wide analysis of H2A.B in mouse ES cells shows that H2A.B is associated with methylated DNA in gene body regions. Moreover, H2A.B-enriched gene loci are actively transcribed. One typical example is that H2A.B is enriched in a set of differentially methylated regions at imprinted loci and facilitates transcription elongation. These results suggest that H2A.B positively regulates transcription elongation by overcoming DNA methylation in the transcribed region. It provides a novel mechanism by which transcription is regulated at DNA hypermethylated regions.